Interactions Between Iron Metabolism and the Endocannabinoid System in Bacterial Infections - Kayle Brenna Dickson; Juan Zhou; Christian Lehmann (Antibiotics, 2025)
Iron is a key nutritional requirement for a variety of physiological functions, and its metabolism is tightly controlled under homeostatic conditions. The endocannabinoid system (ECS) represents an additional physiological system with a key role in maintaining homeostasis that is known for its role in modulating immune responses. Recent research has highlighted intriguing interactions between these systems, including the suppression of iron uptake by the ECS and alterations to the iron-catalyzed Fenton reaction. These interactions are particularly interesting in the context of bacterial infections. As iron is a vital nutrient for bacteria, modulating iron levels using the ECS may be able to control bacterial growth. This review aims to explore the current understanding of how the ECS affects iron homeostasis and its implications for bacterial pathogenesis. In this study, we provide an overview of both iron metabolism and the ECS, focusing on harnessing these systems to develop novel therapeutic strategies to modulate iron metabolism in bacterial infections. By elucidating these complex interactions, we hope to provide new insights into the development of novel treatments for bacterial infections.